2008
DOI: 10.3748/wjg.14.4889
|View full text |Cite
|
Sign up to set email alerts
|

Irritable bowel syndrome subtypes differ in body awareness, psychological symptoms and biochemical stress markers

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
46
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 44 publications
7
46
0
3
Order By: Relevance
“…Our findings that there were no statistically significant differences in QOL and SCL-90-R scores between IBS subtypes are consistent with the results of other previous research (Katsinelos et al, 2009;Park et al, 2009;Jamali et al, 2012). However, Eriksson et al (2008) found that QOL was lower in IBS-C and IBS-M when compared with other subtypes, and showed that the mean psychosocial scores were higher in IBS-M and IBS-C compared with IBS-D. This can be explained by the different types of questionnaires, cultures, and selected subjects.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings that there were no statistically significant differences in QOL and SCL-90-R scores between IBS subtypes are consistent with the results of other previous research (Katsinelos et al, 2009;Park et al, 2009;Jamali et al, 2012). However, Eriksson et al (2008) found that QOL was lower in IBS-C and IBS-M when compared with other subtypes, and showed that the mean psychosocial scores were higher in IBS-M and IBS-C compared with IBS-D. This can be explained by the different types of questionnaires, cultures, and selected subjects.…”
Section: Discussionsupporting
confidence: 93%
“…In this latter study, there was a higher prevalence of psychiatric comorbidity, and IBS patients (bowel habit not specified) had a blunted waking cortisol, which contrasts with findings of most studies. (Eriksson et al, 2008; Patacchioli et al, 2001; Suarez-Hitz et al, 2012)…”
Section: Discussionmentioning
confidence: 99%
“…The study from Eriksson and Andre,[27] who investigated the differences in somatic, psychological and biochemical patterns between the subtypes of IBS, showed that IBS-C patients had higher psychological symptoms and higher prolactin values than IBS-D patients. However, the IBS-D group showed dysfunctional body awareness and higher C-peptide values, probably reflecting an altered adrenergic drive.…”
Section: Discussionmentioning
confidence: 99%